THE NEWBORN’S STATE OF HEALTH, WHICH GOT PROPHYLACTIC ANTISYPHILIS TREATMENT - Pasichnik, I.Р. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
This article is devoted to syphilis as a perinatal problem. The peculiarities of perinatal period of newborns which got prophylactic antisyphilis treatment are carried out in this article.